Actitud del adolescente varón frente al embarazo no deseado en el distrito de Tarapoto, periodo octubre 2005 • febrero 2006 - Torres Pinedo, Clinder (2006)
The present study is simple descriptive, with prospective data collection, whose overall objective was to determine attitudes towards unwanted pregnancy in adolescent males district of Tarapoto, period October 2005 - February 2006. The universe consisted of 65 teenage boys who were in couple pregnant in the study period, who were registered in various health facilities in the city of Tarapoto. In the present study to measure the attitude Likert scale was applied, concluding that 92.3 ° / o of adolescents had an indifferent attitude to an unwanted pregnancy and 7.7 ° / or a favorable attitude, Likewise, the social and educational aspects which have established a relationship with the indifferent attitude found in this study were identified, The social aspect involved in the attitude of male adolescents against unwanted pregnancy mainly refers to 73.8 '/ boys or teenagers interviewed maintain good relationship with their parents and the educational aspect 36.9 "/ or adolescents were enrolled in higher education. Achieving determine the attitude of male adolescents against unwanted pregnancy in the District of Tarapoto and aspects that influence it, results that add to the risk generated by itself in the adolescent pregnancy, as well as in children, constituting a health problem that should not be considered solely in terms of the present but of the future, because of the complications it entails.